2011
DOI: 10.1016/j.rehab.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Education in the management of low back pain. Literature review and recall of key recommendations for practice

Abstract: Therapeutic patient education appears to reduce the negative consequences of fear-avoidance behaviour and thus promotes treatment compliance in LBP patients, from the acute phase onwards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 77 publications
1
35
0
14
Order By: Relevance
“…Koes et al (2010) stress that international guidelines recommend that education of patients suffering from LBP should be aimed at lessening distress and anxiety attached to LBP, and should encourage active recovery. The present study findings are also in agreement with a review in France regarding the positive effects of educational interventions on knowledge and practice of patients suffering from LBP (Dupeyron et al, 2011). Moreover, after the implementation of the present study protocol, significant improvements were revealed in patients' severity of pain and disability scores, which were also maintained throughout the follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Koes et al (2010) stress that international guidelines recommend that education of patients suffering from LBP should be aimed at lessening distress and anxiety attached to LBP, and should encourage active recovery. The present study findings are also in agreement with a review in France regarding the positive effects of educational interventions on knowledge and practice of patients suffering from LBP (Dupeyron et al, 2011). Moreover, after the implementation of the present study protocol, significant improvements were revealed in patients' severity of pain and disability scores, which were also maintained throughout the follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Anti-depressants and muscle relaxants can be used as co-analgesics. The non-medicinal treatments recommended are: patient home exercises learned from a professional, back schools, therapeutic education, cognitive behavioural therapies and multidisciplinary rehabilitation according to the biopsychosocial model which integrates several treatment dimensions: clinical, psychological and social [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the information provided to patients was to limit the chronic nature of the pain and diminish morbidity by providing information on the disease, its prognosis and its evolution, as well as on treatments and their rational use [9]; the purpose of therapeutic education was for patients to acquire knowledge and be able to manage their chronic low back pain on a daily basis [8]. The physiotherapists aimed to teach patients rehabilitation exercises they could do at home.…”
Section: Introductionmentioning
confidence: 99%
“…Une minorité de patients (environ 10 %) engendre à elle seule 85 % de ces coûts [8]. Les facteurs de risque de passage à la chronicité de la lombalgie sont aujourd'hui bien connus.…”
Section: Introductionunclassified
“…Les facteurs de risque de passage à la chronicité de la lombalgie sont aujourd'hui bien connus. Les « drapeaux jaunes » correspondent aux facteurs de risque psychosociaux [8]. Il s'agit de facteurs professionnels (durée de soulèvement de charges, posture professionnelle, insatisfaction au travail), cognitifs (catastrophisme, croyance que la douleur est dommageable), comportementaux (repos prolongé, diminution des activités quotidiennes, évitement des activités normales) et psychologiques (sentiment d'inutilité, dépression, irritabilité, manque de soutien) [28].…”
Section: Introductionunclassified